Pengembangan Media Pembelajaran Interaktif Berbasis Aplikasi Zep Quiz untuk Meningkatkan Hasil Belajar Murid Pada Mata Pelajaran IPAS Kelas V-B SDN Dukuh Kupang V Surabaya - Apriliyah, Putri; Desiningrum, Noviana; Eka Pratiwi, Desi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the validity, practicality, and effectiveness of developing Zep Quiz learning media in the Natural and Social Sciences (IPAS) subject, students’ responses after using the Zep Quiz learning media, students’ activities during the learning process using Zep Quiz, and students’ IPAS learning outcomes after using Zep Quiz on the topic of the human respiratory system. This study employed a Research and Development (R&D) method using the ADDIE development model. The research subjects were 23 fifth-grade students of class V-B at SDN Dukuh Kupang V Surabaya. The results showed that the material expert validation obtained a percentage of 84%, categorized as very valid, while the Zep Quiz media validation obtained a percentage of 97.33%, categorized as very valid. Students’ responses toward the use of Zep Quiz achieved a percentage of 91.41%, categorized as very practical, and students’ learning activities reached 100%, categorized as very practical. The IPAS learning outcomes showed an increase from an average Pretest score of 54.78 to an average Posttest score of 88.47 after using Zep Quiz, with an N-gain value of 0.745, which falls into the high category. Therefore, it can be concluded that the development of Zep Quiz learning media in the IPAS subject is effective in improving the learning outcomes of fifth-grade elementary school students.